The Political Architecture of Dictatorship. - Loveman, Brian (Radical History Review, 2016)
The article talks about politics of dictatorship in Chile focusing on the role of former Chilean President General Augusto Pinochet, September 11, 1973 military coup, and efforts taken bu U.S. government to save the Chilean Democracy. Topics include Chilean exceptionalism, provisions of Code of Military Justice, and role of former president Salvador Allende Gossens. The article talks about Chile government's path to socialism.